The role of a neonatal hypothermia alert device in promoting weight gain in LBW infants. (3rd August 2022) - Azad, Mohammad; Bisht, Surender Singh; Tyagi, Amita; Jaipal, M. L.
Abstract: Background: Neonatal hypothermia is a significant risk factor for preterm and low birth weight (LBW) newborns, especially in India. Kangaroo Mother Care (KMC) is one recommended method of thermal control. A wearable device, TempWatch, has been developed to monitor for and detect hypothermia and to promote KMC for preterm and LBW infants. Purpose: This randomized controlled trial was designed to evaluate TempWatch's impact on weight gain, amount of KMC received, and length of hospital stay for LBW infants as compared to standard care. Methods: Otherwise healthy LBW infants (with birthweights 1500–2300 g) admitted to a KMC ward of a government hospital in New Delhi, India were randomly allocated to a TempWatch group or a control group and wore the device until their time of discharge. 50 infants were enrolled in each group. All participants received standard-of-care temperature monitoring, and those in the control group were monitored using the hand-touch method. Each group also received sixth-hourly temperature monitoring. Infants' daily weight and the number of hypothermia episodes they experienced per day were recorded, and mothers of infants in both groups completed daily KMC diaries. Results: The TempWatch group experienced statistically significant weight gain as compared to the control group (0.06 vs. 0.02 kg, p = .024). There were no statistically significant differences between the groups in the number of hypothermia events detected, the amount of KMC received. Conclusion: TempWatch promotes statistically significant weight gain for LBW infants as compared to standard care.